A reminder that slope-intercept form looks like this:
y = mx + b
And that standard form looks like this:
Ax + By + C = 0 (for A positive)
Let's first solve the problem in slope-intercept form.
y - 4 = (1/2)(x + 3)
First, let's distribute the 1/2
y - 4 = (1/2)x + 3/2
Now, let's bring the -4 over to the right hand side.
y = (1/2)x + 3/2 + 4
Let's change 4 into a fraction over 2.
y = (1/2)x + 3/2 + 8/2
y = (1/2)x + 11/2
That is clearly in slope-intercept form (y = mx + b, as we can identify our m and our b).
To change it to standard form, let's revert back to the original question.
y - 4 = (1/2) (x + 3)
Multiply both sides by 2, to get rid of the fraction.
2(y - 4) = x + 3
And then multiply the 2 out
2y - 8 = x + 3
Now, bring everything over to the right hand side.
0 = x + 3 - 2y + 8
And then combine like-terms, and rearrange.
0 = x - 2y + 11
Therefore, x - 2y + 11 = 0 is clearly in standard form (Ax + By + C = 0).
2006-12-10 10:35:42
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
Slope intercept form:
y=mx+b
y-4=1/2x+3/2
y=1/2x+3/2+8/2
y=1/2x+11/2
Standard form:
Ax+By=C
Multiply 2 on both sides:
2y=x+11
Subtract x from both sides:
-x+2y=11
2006-12-10 18:37:24
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
y-4=1/2(x+3)
y-4=1/2x+3/2
y=1/2x11/2 --> slope-intercept form
-1/2x+y=11/2
-x+2y=11
x-2y=-11 --> standard form
2006-12-10 18:33:35
·
answer #3
·
answered by anonymousperson 4
·
1⤊
1⤋
check out http://www.schoolpiggyback.com ...u'll get other students to do this for u...goodluck : )
2006-12-10 18:30:44
·
answer #4
·
answered by lori b 2
·
0⤊
0⤋